Phase separation: Bridging polymer physics and biology. (February 2019) - Perry, Sarah L.
Abstract: Significant parallels exist between the phase separation behavior of polymers in solution and the types of biomolecular condensates, or 'membraneless organelles, ' that are of increasing interest in living systems. Liquid–liquid phase separation allows for compartmentalization and the sequestration of materials and can be harnessed as a sensitive strategy for responding to small changes in the environment. Here, I review many of the parallels and synergies between ongoing efforts to study and take advantage of phase separation in living versus synthetic materials. Graphical abstract: Image 1 Highlights: Compartmentalization and reaction control can be achieved by phase separation. Phase separation allows for dramatic response to a signal or environmental trigger. Parallels exist between phase-separated materials in living and in synthetic systems. The liquid versus solid nature of the phase-separated material is dictated by the strength of the interactions. Material design is complicated by the diversity of possible interaction motifs.